Adrenal insufficiency in inborn errors of metabolism and vice versa: Case reports and review of the literature - Ariane De Preter; Anne Rochtus; Peter Witters; Daisy Rymen (Molecular Genetics and Metabolism Reports)
Primary adrenal insufficiency (PAI) in children is rare. It is mainly due to monogenetic disorders, with congenital adrenal hyperplasia being the most common cause in the first year of life. Although several inborn errors of metabolism (IEM) have been associated with PAI, increased awareness of PAI in IEM among both metabolic specialists and endocrinologists may improve patient outcomes. Here, we present a case series of patients with PAI and an IEM. Through a literature review, we discuss the various IEM that have been associated with adrenal insufficiency and explore the pathophysiological mechanisms linking these IEM to PAI. Based on the available data, pitfalls in the diagnosis of PAI in IEM are discussed and recommendations for early diagnosis are suggested. In addition, a non-exhaustive list of susceptible IEM was elaborated to encourage screening for PAI in IEM and vice versa.